Identification and subcellular localization analysis of two rubber elongation factor isoforms on Hevea brasiliensis rubber particles - Dai, Longjun (Plant physiology and biochemistry : PPB, 2017)
Copyright © 2016. Published by Elsevier Masson SAS.